Effect of Different DMSO Concentrations on Dynamics of Hormone-Stimulated Changes in Transmembrane Potentials of Isolated Rat Hepatocytes During Assessment with Fluorescent Probes - Kavok, N. S.; Borovoy, I. A.; Malyukina, M. Yu. (Problems of Cryobiology and Cryomedicine, 2011)
Using fluorescent microscopy technique, the changes of transmembrane potential of plasma and mitochondrial membranes of the isolated rat hepatocytes has been estimated under the stimulation by catecholamines against the background influence of dimethyl sulfoxide (DMSO) cryoprotectant. The fluorescence intensity of probe H-510 based on 3, 3-dialkylcarbocyanine bromide (where alkyl was used as ethyl) was a measure of the plasmatic potential value, whereas the fluorescence intensity of mitochondrial JC-1 dye aggregates was used to estimate a mitochondrial potential value. It was shown that the dynamics of fluorescent changes reflected the diphase character of hyperpolarization of cellular membrane under influence of adrenaline and alpha-agonist, phenylephrine. Stimulative effect of phenylephrine on cellular potential in 2% DMSO presence is observed in the first phase of cellular response and is absent in the second one. The toxic concentration (8%) of the cryoprotectanttotally blocks the alpha-agonist action. Hormone stimulative effect on mitochondrial potential was not observed even at 2% cryoprotectant concentration. Thus, the data obtained reveal the influence of DMSO on the initial stages of signal transduction.